ثقافة العمل في الجزائر: مقاربة وصفية تحليلية - لعوارم، مهدي Awarem, Mahdi (جامعة قاصدي مرباح - ورقلة, 2019)
The aim of this article is to examine the reality of the culture of work in Algerian society by analyzing some of the factors that influence the work culture of the Algerian worker and to highlight the most important characteristics that characterize them, especially in the light of a number of economic, social and cultural changes. Especially the institutions of the public sector or the private sector, with some paradoxes, namely, the call of the Authority to the need to diversify the national economy and open the way to investment for young people, but the current reality proves in more than The approach of the curriculum in the management of the Algerian economic system is not clearly indicative of the application of the market economy system according to its constituent elements, in view of the continuation of the culture of dependence, the spread of the culture of quick profit and practices related to the informal economy and other manifestations of the negative culture of work where absent initiative Risk and creativity and often replaced by a negative culture, From this point of view, this article is based on a descriptive approach and analytical method of the factors that are problematic and influential in the work culture of Algerian society.
تهدف هذه المقالة للبحث في واقع ثقافة العمل في المجتمع الجزائري، وذلك بتحليل بعض العوامل المكونة والمؤثرة في ثقافة العمل بالنسبة للعامل الجزائري، وتبيان أهم الخصائص التي تتميز بها خاصة في ظل جملة من التغيرات الاقتصادية والاجتماعية، التي يشهدها المجتمع الجزائري عموما وفضاءات العمل في شتى المؤسسات، سواء المؤسسات التابعة للقطاع العام أو القطاع الخاص، مع وجود بعض المفارقات والمتمثلة أساسا في دعوة السلطة إلى ضرورة تنويع الاقتصاد الوطني وفتح المجال نحو الاستثمار، إلا أن الواقع الراهن يثبت في أكثر من دلالة على أن النهج المنتهج في تسيير المنظومة الاقتصادية في الجزائري غير واضح بشكل يدل على تطبيق نظام اقتصاد السوق وفق مقوماته المؤسس عليها، أمام استمرار ثقافة الاتكالية، وانتشار ثقافة الربح السريع والممارسات التي لها علاقة بالاقتصاد غير الرسمي وغيرها من مظاهر تشكل ملامح لثقافة عمل سلبية أين تغيب روح المبادرة والمخاطرة والإبداع وحلت محلها في كثير من الأحيان، ثقافة سلبية 'اقفز تعيش، نافيقي، ليزافار...، من هذا المنطلق فإن هذه المقالة تقوم على مقاربة وصفية وكيفية تحليلية للعوامل المشكلة والمؤثرة في ثقافة العمل بالمجتمع الجزائري.
Keywords: قانون العمل -- ثقافة العمل -- قيم العمل -- الدستور الجزائري -- الجزائر